Necrotizing enterocolitis: Evaluation of risk and protection factors concerning the severity and outcome of the disease (Research, Society and Development, 2023)
Objective: To correlate the prenatal and neonatal risk and protection factors to the severity and outcome of Necrotizing Enterocolitis (NEC). Methodology: 88 medical records were evaluated over a 10-year period retrospectively, but 11 were excluded. The severity of NEC was classified according to the criteria of Bell et al. (1978) and the pre and postnatal risk factors were correlated to the stages of disease severity, as well as to death. Results: 77 cases evaluated showed a relationship with severity to the time on oxygen therapy, time on mechanical ventilation (MV), early sepsis, the use of gastric mucosal protectors and the clinical severity of the newborns (NB), represented by the Score SNAPPE-II. The highest number of NB fed with human milk was encountered in stage I. Time spent on MV (p=0.049), early sepsis (p=0.014), hypoglycemia (p=0.047) and the most serious forms of NEC (stage III versus I – odds ratio de 5.4 and p-value=0.010), were correlated to the death. Conclusion: the smaller and most serious NB went on to develop the worst stages of the disease. Time on MV, early sepsis, hypoglycemia and the most serious forms of NEC were correlated with death. There was noted a possible protective role of human milk in terms for development of the most severe stages of NEC.